The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1103/physreva.87.043824
|View full text |Cite
|
Sign up to set email alerts
|

Influence of geometry and topology of quantum graphs on their nonlinear optical properties

Abstract: We analyze the nonlinear optics of quasi one-dimensional quantum graphs and manipulate their topology and geometry to generate for the first time nonlinearities in a simple system approaching the fundamental limits of the first and second hyperpolarizabilities. We explore a huge configuration space in order to determine whether the fundamental limits may be approached for specific topologies, independent of molecular details, when geometry is manipulated to maximize the intrinsic response. Changes in geometry … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 49 publications
0
63
0
Order By: Relevance
“…2 shows the full ground state wavefunction ψ 0 (x, y) for the one-prong graph, where it is seen that the electron wavefunction along the main direction has a kink caused by the presence of the prong. We note that computation of quantum graphs requires solutions in both x and y directions [12] but the x direction is the dominant contributor to the response for this graph. Fig.…”
Section: Figmentioning
confidence: 99%
“…2 shows the full ground state wavefunction ψ 0 (x, y) for the one-prong graph, where it is seen that the electron wavefunction along the main direction has a kink caused by the presence of the prong. We note that computation of quantum graphs requires solutions in both x and y directions [12] but the x direction is the dominant contributor to the response for this graph. Fig.…”
Section: Figmentioning
confidence: 99%
“…For the remainder of this work all calculations of the hyperpolarizability will be normalized to this maximum and therefore represent the intrinsic value β int = β/β max , which is invariant under a global length scale change. Through extensive potential optimization [10][11][12] it has become clear that there exists an apparent limit to the hyperpolarizability of real systems which is 0.7089β max , while molecules engineered for nonlinear-optical applications are often a factor of 30 below the fundamental limit. However, by sampling random transition moments and energy spectra constrained only by the sum-rules, Shafei, et al, [6] showed that the fundamental limit is achievable in principal only by energy spectra which scale as n 2 or faster.…”
Section: B Characteristics Of the Optimum Hyperpolarizabilitymentioning
confidence: 99%
“…This paper is presented as follows. Section 2 begins with a concise summary of the standard method we developed for calculating the hyperpolarizability tensors of a large ensemble of topologically equivalent graphs whose geometry is varied in a Monte Carlo algorithm 34,46,35,36 . We then invoke the motif method 36 to determine the characteristic function of the compressed delta atom in Section 3, as preparation for all subsequent work.…”
Section: Rljnopmmentioning
confidence: 99%
“…We have used a general Monte Carlo method that explores a very large configuration space to discover structures with optimum nonlinearities, which has been extensively reviewed in our prior publications for undressed graphs 34,46,35,36 . We start by randomly selecting vertices in 2D space, connecting them with metric edges representing a desired topology (eg, a loop or star), endowing them with single-electron dynamics, and then solving for the exact eigenstates and spectra of the entire graph by first computing the edge states that are eigenfunctions of the Hamiltonian on each edge with the same spectrum as all other edges and then using an appropriate union operation on edge states to create an eigenstate of a Hilbert space that is a direct sum of those on each edge 34 :…”
Section: Calculation Of Optical Nonlinearities Of Quantum Graphsmentioning
confidence: 99%